Local recurrences for mixed germ cell tumors without scrotal violation, is metastatic disease around the corner? A case report - Georges Abi Tayeh; Constance Michel; Xavier Durand (Future Science OA, 2024)
We hereby report the case of a 40-year-old male, who initially underwent a left inguinal orchiectomy for a stage Is mixed germ cell tumor achieving an R0 status. His follow-up is mainly noticeable for many recurrences affecting exclusively the inguinal and suprapubic soft tissues. The recurrences occurred early, and almost always contained immature tissue upon pathologic reading, which has never been described in the medical literature before.